Statistical quality control study Sterling Paper Products Enterprises Inc. - Abanto, Ray Anthony A. (College of Engineering, 2002)
Sterling Paper Products Enterprises, Inc is a large company that manufactures paper products such as writing paper, notebooks and even paper cups. It was formed in 1960 at Caloocan City. A quality control study was performed on Sterling Paper Products Enterprises Inc. during the period from August to September 2002. Before the study was conducted it was found that a lot of waste was generated by the company due to scrapping of material and downgrading. The four main problems that were investigated were the discoloration on printed sheets, presence of dirt and smudges on printed sheets, poor welds in the cup-forming process, and incorrect dimensions of sheets in the sheeting process. The problems were identified through the use of the Pareto Analysis wherein the processes that contribute to the most rejects were identified. Stream Diagnostic Charting was also used to identify the relationships of the problems related to the processes identified in the Pareto Analysis. The four problems were derived from this chart. Then an Ishikawa Diagram was constructed for each problem to pinpoint possible causes for each. A p chart was constructed for the statistical process control analysis for the discoloration on printed sheets. It was found that the process was under statistical control for this problem. Also, the p chart passed Shewhart's eight tests for control charts when it was applied. For the presence of dirt and smudges, a p chart was also constructed. In the p chart, five points were beyond the control limits, though they passed Shewhart's eight tests. Additional in-depth analysis was done on this defect to find the assignable causes that can account for the outliers. The main causes identified were the failure of the blocking powder to coat the printed sheets, and the actual mixture of the paint. The group then recommended that an evaluation of the supplier of the blocking powder be done, as well as an evaluation of the paint used. The optimal amount of coating powder should be determined. The determined amount should be controlled. Paint mixing practices should also be standardized. The group recommended that the company determine the optimal amount of water and paint present in the dampening solution. Regular machine maintenance was also deemed necessary in order to reduce the amount of foreign components to mix with the prints. A concrete sampling plan both for the discoloration and presence of dirt and smudges on the printed sheets. The group's designed sampling plan suggested uses a sample of size 125 and an acceptance number of 10. For the poor welds in the cup-forming process, an np chart was constructed. It showed that there were five points beyond the control limits, though only three of these have assignable causes. When the control limits were revised, it was found that the points failed Shewhart's fifth test. Assignable causes were accounted for these, and it was found that the main cause for these was the incorrect settings for the machine. After revising the control limits, it was found that there were still points beyond the control limits without assignable causes. The deviations were determined to be due to the process itself and a thorough evaluation of the machine settings was recommended. The temperature for the two air seams, the air pressure for the vacuum compressor and the silicon oil spray pause should be determined. These were the main factors that affect the formation of the cup. For the incorrect sheet dimensions, it was found that the process was in statistical control through the analysis of the Xbar and R chart constructed for it. No points were beyond the control limits, and it also passed Shewhart's eight tests. It was recommended though, that guidelines in placing the rolls in front of the sheeting machine be made. This was suggested to avoid misalignment of the rolls which produced an improperly cut sheet. As for the process capability analysis of the sheeting process, it was found out that it is capable, based on the computations of the process capability potential (Cp) and the process capability (Cpk). The value of Cp for both the length and the width are both 1.88. The computed process capability ratio implies that the company has an acceptable process, when compared to the minimum process capability ratio used by the industry, which is 1.33. Also, the Cpk for both the width and the length are the same, and the value is 1.88. Cpk should be equal to Cp for the process to be centered; meaning that the actual process mean coincides with the specification. Since Cpk is equal to Cp, the process is centered. This implies that the potential capability of the process is reached, since Cpk measures the actual capability of the process.